C11 Behavioural studies in Libechov minipigs with huntington's disease; changes in behaviour, motor skills and learning. (13th September 2016) - Bohuslavova, Bozena; Kucerova, Sarka; Macakova, Monika; Klempir, Jiri; Lavickova, Romana; Krupicka, Radim; Kauler, Jan; Baxa, Monika; Ellederova, Zdenka; Motlik, Jan
Abstract : Background: Huntington's disease (HD) is characterised by involuntary chorea like movements, poor balance, slurred speech, difficulty swallowing, personality change and difficulty thinking manifesting in the middle age of the patients. Changes in behaviour, motor skills and learning correlate with progression of the disease. Thus it is necessary to monitor these changes in new animal models. In 2009, we have generated transgenic minipigs (TgHD) expressing N-terminal (548 aa) part of human huntingtin (Htt) containing 126 CAG/CAA repeats. Aims: To follow disease development in TgHD minipigs of F0, F1 and F3 generation using motoric and behavioural tests. Methods: In order to follow behavioural and motoric changes we introduced stability pull back test, balance bean, seesaw test, up and down step test, and tunnel test. We also initiated to use accelerometers to monitor walking differences. Results: We observed higher fear or inability to perform certain tests, delayed learning period mainly in situations inducing stress in our oldest TgHD animals (F0, F1 generations). The significant difference between WT and TgHD minipigs was noticed in the ability to step on and to cross the elevated balance beam. Pull back stability test showed a significant difference in TgHD animals. Wobbly movements of back legs were observed in the five years old animals. The weight of all the oldest animals dropped in 10% in the last year. Conclusions: The minipig model starts to show a motoric impairment phenotype, and thus to be a promising model for preclinical testing of new therapeutic approaches of HD. Acknowledgement: "The research leading to these results has received funding from the Norwegian Financial Mechanism 2009–2014 and the Ministry of Education, Youth and Sports Project under Contract no. MSMT-28477/2014" (7F14308/2014), and National Sustainability Programme, project number LO1609 (Czech Ministry of Education, Youth and Sports) and RVO: 67985904